VDC_100102370166.0X000001. Issue 4 (April 2018) - Strosberg, David S.; Quinn, Kristen M.; Abdel-Misih, Sherif R.; Harzman, Alan E.
Our objective was to investigate the number and classify surgical operations performed by general surgery residents and compare these with the updated Surgical Council on Resident Education (SCORE) curriculum. We performed a retrospective review of logged surgical cases from general surgical residents who completed training at a single center from 2011 to 2015. The logged cases were correlated with the operations extracted from the SCORE curriculum. Hundred and fifty-one procedures were examined; there were 98 "core" and 53 "advanced" cases as determined by the SCORE. Twenty-eight residents graduated with an average of 1017 major cases. Each resident completed 66 (67%) core cases and 17 (32%) advanced cases an average of one or more times with 39 (40%) core cases and 6 (11%) advanced cases completed five or more times. Core procedures that are infrequently or not performed by residents should be identified in each program to focus on resident education.